Estimation of Minimum Biofilm Eradication Concentration (MBEC) on In Vivo Biofilm on Orthopedic Implants in a Rodent Femoral Infection Model - Okae, Yu; Nishitani, Kohei; Sakamoto, Akio; Kawai, Toshiyuki; Tomizawa, Takuya; Saito, Motoo; Kuroda, Yutaka; Matsuda, Shuichi (Frontiers in Cellular and Infection Microbiology, 2022)
The formation of a biofilm on the implant surface is a major cause of intractable implant-associated infection. To investigate the antibiotic concentration needed to eradicate the bacteria inside a biofilm, the minimum biofilm eradication concentration (MBEC) has been used, mostly against in vitro biofilms on plastic surfaces. To produce a more clinically relevant environment, an MBEC assay against biofilms on stainless-steel implants formed in a rat femoral infection model was developed. The rats were implanted with stainless steel screws contaminated by two Staphylococcus aureus strains (UAMS-1, methicillin-sensitive Staphylococcus aureus; USA300LAC, methicillin-resistant Staphylococcus aureus) and euthanized on days 3 and 14. Implants were harvested, washed, and incubated with various concentrations (64–4096 μg/mL) of gentamicin (GM), vancomycin (VA), or cefazolin (CZ) with or without an accompanying systemic treatment dose of VA (20 μg/mL) or rifampicin (RF) (1.5 μg/mL) for 24 h. The implant was vortexed and sonicated, the biofilm was removed, and the implant was re-incubated to determine bacterial recovery. MBEC on the removed biofilm and implant was defined as in vivo MBEC and in vivo implant MBEC, respectively, and the concentrations of 100% and 60% eradication were defined as MBEC100 and MBEC60, respectively. As for in vivo MBEC, MBEC100 of GM was 256–1024 μg/mL, but that of VA and CZ ranged from 2048–4096 μg/mL. Surprisingly, the in vivo implant MBEC was much higher, ranging from 2048 μg/mL to more than 4096 μg/mL. The addition of RF, not VA, as a secondary antibiotic was effective, and MBEC60 on day 3 USA300LAC biofilm was reduced from 1024 μg/mL with GM alone to 128 μg/mL in combination with RF and the MBEC60 on day 14 USA300LAC biofilm was reduced from 2048 μg/mL in GM alone to 256 μg/mL in combination with RF. In conclusion, a novel MBEC assay for in vivo biofilms on orthopedic implants was developed. GM was the most effective against both methicillin-sensitive and methicillin-resistant Staphylococcus aureus, in in vivo biofilms, and the addition of a systemic concentration of RF reduced MBEC of GM. Early initiation of treatment is desired because the required concentration of antibiotics increases with biofilm maturation.